STUDY OF SHATAPUSHPA CHOORNA AND SAHACHARADI TAILA IN OLIGOMENORRHOEA (AYUSHDHARA, 2020)
The abnormal menstrual flow indicates heavy menses and scanty menstrual flow, both in amount and duration with associated symptom of pain in lower abdomen or back or vagina and can be counted as Vataja Rajodushti, Kshinartava and Artavakshaya in Ayurveda classics. Aims and objectives: In Ayurvedic classic, Uttarabasti is indicated in Yonivyapada (gynecological problems), Artava nasha (secondary amenorrhea), Artava Dosha (menstrual disorder) etc. Vatadosha is the prime cause of Yoni vyapada. Uttara basti has Vatashamak as well as Ropana and Shodhana property. Sahacharadi taila is indicated in Vata disorders including oligomenorrhea. Shatapushpa (Anethum sowa Kurz.) Churna is Arthavajanan. Materials and methods: From OPD 30 patients were selected randomly and divided into 15 patients in each Group A and Group B. Group A was given Shatapushpa churna orally 3times per day for 3 months and Sahacharadi taila Uttaravasti for 3 consecutive cycles. Group B was given placebo. Results were analysed by statistical analysis. Results and conclusion: Properties of Shatapushpa churna, Saacharadi taila with Uttarbasti might improve menstrual irregularities and bring down to normalcy.